2015
DOI: 10.1002/14651858.cd008327.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for metabolic bone disease in children with chronic kidney disease

Abstract: Background Bone disease is common in children with chronic kidney disease (CKD) and when untreated may result in bone deformities, bone pain, fractures and reduced growth rates. This is an update of a review first published in 2010. Objectives This review aimed to examine the benefits (improved growth rates, reduced risk of bone fractures and deformities, reduction in PTH levels) and harms (hypercalcaemia, blood vessel calcification, deterioration in kidney function) of interventions (including vitamin D prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The Cochrane review has not shown any significant difference in hypercalcemia risk with vitamin D preparations compared with placebo, but 1 study showed a significantly greater risk of hypercalcemia with i.v. calcitriol administration 136 . No difference in growth rates was detected between different vitamin D analogs or use of oral or i.v.…”
Section: Chapter 42: Treatment Of Abnormal Pth Levels In Ckd-mbdmentioning
confidence: 84%
See 2 more Smart Citations
“…The Cochrane review has not shown any significant difference in hypercalcemia risk with vitamin D preparations compared with placebo, but 1 study showed a significantly greater risk of hypercalcemia with i.v. calcitriol administration 136 . No difference in growth rates was detected between different vitamin D analogs or use of oral or i.v.…”
Section: Chapter 42: Treatment Of Abnormal Pth Levels In Ckd-mbdmentioning
confidence: 84%
“…All of the above studies were conducted in adults. A recent Cochrane review examined vitamin D therapy for bone disease in children with CKD G2 to G5 on dialysis 136 . Bone disease, as assessed by changes in PTH levels, was improved by all vitamin D preparations regardless of route or frequency of administration.…”
Section: Chapter 42: Treatment Of Abnormal Pth Levels In Ckd-mbdmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal phosphate levels result in the change in osteolysis and osteogenesis, and disordered mineral metabolism aggravates the change in serum phosphate levels. When untreated for a long time, they may cause renal osteodystrophy and bone disease (29). Meanwhile, CKD-MBD has different types such as high and low turnover bone diseases (4).…”
Section: Discussionmentioning
confidence: 99%
“…A second document in parallel with this one covers treatment recommendations for the assessment of vitamin D status, optimal levels of 25(OH)D and its monitoring and recommendations for native vitamin D supplementation [12]. The recent Cochrane Review [13] (Table 1) and evidence tables from the Kidney Disease: Improving Global Outcomes (KDIGO) CKD-MBD update document [26] were used to evaluate all available studies and, in addition, the core working group has performed an extensive literature review as described below. Most studies are small, include different vitamin D analogues, variable starting and maintenance doses and routes of administration and rely predominantly on surrogate endpoints, in particular PTH, with few data available on patientcentred outcomes such as fracture risk and growth.…”
Section: | | | | | | | | | | | | | | | | | | | | | | | | | | | | | mentioning
confidence: 99%